Mycorrhizal fungi isolated from native terrestrial orchids of pristine regions in Córdoba (Argentina) - Fernández Di Pardo, Agustina; Chiocchio, Viviana M.; Barrera, Viviana Andrea; Colombo, Roxana P.; Martinez, Alicia E.; Gasoni, Amelia Laura; Godeas, Alicia M. (Universidad de Costa Rica, 2025)
Orchidaceae is a highly dependent group on the Rhizoctonia complex that includes Ceratorhiza, Moniliopsis, Epulorhiza and Rhizoctonia, for seed germination and the development of new orchid plants. Thus, the isolation and identification of orchid mycorrhizal fungi are important to understand the orchid-fungus relationship, which can lead to the development of efficient conservation strategies by in vivo germination of seeds from endangered orchid plants. The aim of our work was to isolate and characterize the different mycorrhizal fungi found in roots of terrestrial orchids from Córdoba (Argentina), and, to learn about the natural habit and fungal associations in the Chaco Serrano woodland pristine region. In this study, bloomed orchid root and rhizosphere soil samples were obtained in two times from Valle de Punilla during spring of 2007; samples were kept in plastic bags until processed within 48 hours, and mycorrhizal condition confirmed assessing peloton presence. A total of 23 isolates of the orchideous mycorrhizal Rhizoctonia complex were obtained. The isolates were studied based on morphological characters and ITS-rDNA sequences. Morphological characteristics as color of colonies, texture, growth rate, hyphal diameter and length and presence of sclerotia were observed on culture media. To define the number of nuclei per cell, the isolates were grown in Petri dishes containing water-agar (WA) for three days at 25°C and stained with Safranine-O solution. The mycorrhizal fungi were grouped into binucleate (MSGib, 10 isolates) and multinucleate (MSGim, 13 isolates) based on morphological characteristics of the colonies. We obtained 1The ITS1-5.8s-ITS4 region that was amplified using primers ITS1 and ITS4. Based on DNA sequencing, isolates Q23 and Q29 were found to be related to species of Ceratobasidium. Isolates Q24 and Q4 were related to the binucleated anastomosis group AG-C of Rhizoctonia sp. The rest of the isolates grouped in the Ceratobasidium clade without grouping. From our knowledge this is the first report of the association of the AG-C testers with terrestrial orchids. A high specificity was observed in the symbiotic relationship. As the mycorrhizal fungal isolates were obtained from native orchids, they could be incorporated in conservation programes of endangered orchids in Argentina.